Western Hemisphere Free Trade Area : an overview of the issues (ECLAC SantiagoCL, 1992)
Examines the issues that need to be addressed when considering the formation of a Western Hemispheric Free Trade Area (WHFTA) viz. global issues; trade liberalization in the Western Hemisphere; estimated impact from trade liberlization at country and sector levels; negotiating agenda and perspectives; and, the transition. Focuses on the costs and benefits of a WHFTA as well as on practical considerations relevant to a process of hemispheric trade liberalization.
DC